PENINGKATAN KETERAMPILAN MEMPARAFRASEKAN PUISI DENGAN PEMANFAATAN MEDIA GAMBAR ILUSTRASI - ANITA ANITA (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2022)
The background of this research problem is the low learning outcomes of Indonesian language skills aspects of paraphrasing poetry in class VI A Madrasah Ibtidaiyah Negeri 3 (MIN 3) Purbalingga, the academic year 2021/2022. The low learning outcomes are partly due to the lack of student understanding because the teacher has not utilized media in the learning process. The author uses illustrated media to overcome this problem by considering that the illustration media is simple, practical, easy to understand, and effective. The purpose of this research is to improve the students' skills in paraphrasing poetry by utilizing the media of illustration images. This research is a best practice. The subjects in this study were 25 students of class VIA MIN 3 Purbalingga. The object of this research is the use of illustrated media to improve poetry paraphrasing skills. The data collection technique used participant observation and skill assessment using the rubric for assessing poetry paraphrasing skills. This research was carried out with a preparatory step, the teacher distributed illustrated media, students observed pictures, students collected vocabulary, students developed vocabulary into lines of poetry, and students changed poetry into descriptive essays or narratives. The results of this study prove that the use of illustrated media can improve students' skills in paraphrasing poetry. Based on the data from the skills assessment, it shows that as many as 18 students or as many as 72% of students have completed learning. ABSTRAKLatar belakang masalah penelitian ini adalah rendahnya hasil belajar Bahasa Indonesia aspek keterampilan memparafrasekan puisi di kelas VI A Madrasah Ibtidaiyah Negeri 3 (MIN 3) Purbalingga, tahun pelajaran 2021/ 2022. Rendahnya hasil belajar ini antara lain disebabkan oleh kurangnya pemahaman siswa dikarenakan guru belum memanfaatkan media dalam proses pembelajaran. Penulis menggunakan media gambar ilustrasi untuk mengatasi masalah tersebut dengan pertimbangan media gambar ilustrasi itu sederhana, praktis, mudah dipahami, dan efektif. Tujuan dari penelitian ini adalah untuk meningkatkan keterampilan peserta didik dalam memparafrasekan puisi dengan memanfaatkan media gambar ilustrasi. Penelitian ini merupakan best practice. Subjek dalam penelitian ini adalah peserta didik kelas VIA MIN 3 Purbalingga sebanyak 25 anak. Objek dalam penelitian ini adalah pemanfaatan media gambar ilustrasi untuk meningkatkan keterampilan memparafrasekan puisi. Teknik pengumpulan data menggunakan observasi partisipan dan penilaian keterampilan menggunakan rubrik penilaian keterampilan memparafrasekan puisi. Penelitian ini dilakukan dengan langkah persiapan, guru membagikan media gambar ilustrasi, peserta didik mengamati gambar, peserta didik mengumpulkan kosakata, peserta didik mengembangkan kosakata menjadi baris puisi, dan peserta didik mengubah puisi menjadi karangan deskripsi atau narasi. Hasil penelitian ini membuktikan pemanfaatan media gambar ilustrasi mampu meningkatkan keterampilan peserta didik dalam memparafrasekan puisi. Berdasarkan data hasil penilaian keterampilan menunjukkan sebanyak 18 peserta didik atau sebanyak 72% peserta didik telah tuntas belajar.